Rancangan Pengurangan Waste Proses Penyusunan Dokumen: Studi Kasus pada Service Level Agreement Perusahaan Rokok - Arvin Oktovianus; I Nyoman Sutapa (Jurnal Titra, 2020)
The Research is held in a manufacturing company that manufactures cigarettes. The problem that occurs in the company is the ineffectiveness of the process of drafting documents such as organization chart and job description along with job evaluation at the Service Level Agreement in the Compensations & Benefits (C&B) department as the result of waste. Transportation waste occurs as a result of the form of the documents is in the form of hardcopy. Overprocessing waste occurs as a result of operator error in doing the work, so it is necessary to repeat the work process. The analysis technique used in this research is Value Stream Mapping (VSM) which is one of the tools of lean manufacturing. VSM is used as a tool to identify waste from the classification of value added activity and non-value added activity. The elimination of transportation waste is done by using an Electronic Document (e-doc). The elimination of overprocessing waste is done by setting a job family template, setting a complete document checklist, and checking spelling through excel.